Evaluation of Parenchymal Neuro-Behçet Disease by Using Susceptibility-Weighted Imaging - Albayram, S. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Neurologic involvement in Behçet disease, also known as NBD, is one of the most devastating manifestations of the disease. The precise pathologic mechanism of parenchymal NBD lesions has not been established. We evaluated lesion characteristics and probable venous hemorrhage in parenchymal NBD by using SWI, and we compared the imaging results with conventional MR imaging sequences. MATERIALS AND METHODS: We performed cranial MR imaging by using a 1.5T scanner in 23 patients with a definitive diagnosis of parenchymal NBD. We compared the proportion of lesion detection and the performance of hemorrhagic detection with the T2 FSE, T2*GE, and SWI magnitude, and SWI mIP by using the χ(2) test. RESULTS: The proportion of lesion detection with both SWI magnitude and SWI MinMIP was significantly larger than that with T2*GE. The proportions of lesion detection among all other pairs of methods were not significantly different according to the corresponding P value (χ(2) = 17.4929, df = 3, P = .0006). Proportions of hypointense hemorrhagic lesions with T2 FSE and T2*GE were not significantly different, and likewise for the proportions of hypointense hemorrhagic lesions with SWI magnitude and SWI mIP. In contrast, the proportions of hypointense hemorrhagic lesions with SWI magnitude and SWI mIP were significantly larger than that with T2 FSE and T2*GE (χ(2) = 108.5396, df = 3, P < .0001). CONCLUSIONS: Most of the lesions in parenchymal NBD were found to be hemorrhagic with SWI, supporting the proposed venous theory in pathology. In addition, compared with T2 FSE and T2*GE sequences, SWI was more successful in the determination of widespread involvement of the disease, particularly in nonchronic cases.